2009
DOI: 10.1007/s12020-009-9210-2
|View full text |Cite|
|
Sign up to set email alerts
|

Thyroid hormones alterations during acute liver failure: possible underlying mechanisms and consequences

Abstract: Thyroid hormones are now recognized to change in different disease states with important consequences on severity and prognosis of disease. However, little is known about thyroid hormones' alterations in acute liver failure (ALF). To study the changes in thyroid hormones and cardiac thyroid receptors during ALF, we subjected seven female pigs to surgical liver devascularization. Liver function biochemical markers, thyroid hormones, endogenous opioids, malondialdehyde (MDA), and interleukins 1 and 6 were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Although total hormone levels were changed significantly in the presented ALF cohort, free thyroid hormones did not differ between SR and NSR patients. This finding is in line with ALF in a pig model, where serum thyroxin T3 and T4 levels markedly decrease after ALF induction, whereas fT3 and fT4 levels did not change [ 19 ]. Reduction of total but not free hormone concentrations in NSR compared to SR patients might imply a deficit of transport proteins produced by the liver (i.e.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although total hormone levels were changed significantly in the presented ALF cohort, free thyroid hormones did not differ between SR and NSR patients. This finding is in line with ALF in a pig model, where serum thyroxin T3 and T4 levels markedly decrease after ALF induction, whereas fT3 and fT4 levels did not change [ 19 ]. Reduction of total but not free hormone concentrations in NSR compared to SR patients might imply a deficit of transport proteins produced by the liver (i.e.…”
Section: Discussionsupporting
confidence: 73%
“…In a study of Kostopanagiotou et al . involving a pig model of ALF, serum T3 and T4 levels markedly decreased after induction of ALF, whereas fT3 and fT4 levels did not change [ 19 ]. In summary the above described data suggests that ALF leads to changes of thyroid serum parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The low T3 status as an independent predictor of death was also reported in patients with acute myocardial infarction ( Friberg et al, 2002 ), cardiac arrest ( Iltumur et al, 2005 ), heart failure ( Pingitore et al, 2005 ) and respiratory failure from pulmonary disorders ( Scoscia et al, 2004 ). Analogous fi ndings concerning thyroid hormone changes (with low T3 levels) in other diseases, like traumatic brain injury ( Cernak et al, 1999 ), acute liver failure ( Kostopanagiotou et al, 2009 ) and even chronic obstructive pulmonary disease ( Karadag et al, 2007 ), have been reported. Finally, low fT3 levels are associated with the increase of disease severity and higher mortality among critically ill patients, especially in intensive care units ( Chinga-Alayo et al, 2005 ).…”
Section: Discussion ▼mentioning
confidence: 69%
“…This was due to decreased hepatic uptake and type-1 deiodinase activity (D1), which converts T4 to T3. [ 5 ] Liver disease is also associated with increase in inflammatory cytokines that negatively affect hypothalamothyroid axis,[ 11 21 ] which may explain lower TSH levels (statistically not significant) observed in patients with liver disease as compared to controls in this study. Other studies have reported higher levels of TSH in CLDs,[ 8 22 ] but these studies have not excluded patients with overt thyroid dysfunction, which we have excluded in this study before analysis.…”
Section: Discussionmentioning
confidence: 82%